Transurethral resection of bladder tumour as day-case surgery: Evidence of effectiveness from the UK Getting it Right First Time (GIRFT) programme. (May 2020) - Gray, William K; Day, Jamie; Briggs, Tim WR; Harrison, Simon
We aimed to investigate outcomes of transurethral resection of bladder tumour (TURBT) surgery when performed as day-case surgery compared to outcomes for patients who stayed ⩾ 1 night in hospital. Data were taken from the 2017–2018 Hospital Episodes Statistics data set, which contains data for all TURBT procedures conducted within the National Health Service in England. Data were categorised as those seen as day-cases and those that involved an overnight stay. Of 19, 383 TURBT procedures, 3466 (17.9%) were classified as day-case surgery. Those who had an overnight stay were significantly older and were significantly more likely to be male, and have significantly greater frailty and comorbidity. After adjusting for confounders, those with an overnight stay had significantly poorer outcomes with regard to mortality and emergency readmission rates. Comparing trusts with the highest and lowest rate, of overnight stay, there were no differences in the profiles of the patients seen or in outcomes. Patients undergoing TURBT as day-case surgery have at least as good outcomes as those having an overnight stay. Investigation of the technical quality of the tumour resection, patient experience and quality of life after day-case surgery for TURBT would provide further insight. Evidence level: 2b